Assessing the energy performance certification effectiveness for the Spanish building stock in response to recent climate change data - Sarabia-Escriva, Emilio-José; Jiménez-Navarro, Juan-Pablo; Soto-Francés, Víctor-Manuel; Pinazo-Ojer, José Manuel (Elsevier, 2024)
This comprehensive study analyses the energy demand for heating and cooling in the building stock across different climatic zones in Spain, incorporating the effects of weather evolution over the past 30 years (from 1992 to 2022). In evaluating 7200 cases across four climatic years and six climatic zones which include six Spanish cities, the analysis examines the construction characteristics of the building stock. The focus is on the thermal envelop properties under two scenarios: the current state and a renovated state that complies with the new Spanish building code (in agreement with the EPBD EU-Directive EU/2024/1275). The study’s findings reveal potentially significant changes in energy demand due to climate. The heating demand decreases significantly due to increasing temperatures ranging from 17% in Madrid up to 37% in Almería. This effect is contrasted by a substantial increase in cooling demand, which has surged 223% in Barcelona, a surge closely linked to higher summer temperatures. The paper concludes that the current energy certification scheme fails to provide a real overview of the energy performance and needs of buildings in Spain. In particular, it underestimates actual sensible cooling demand by 56% in Barcelona and 41% in Almería. Additionally, the failure of existing building regulations to address the issue of indoor overheating is proven.
Keywords: Edificios - Conservación de la energía; Building energy efficiency; Building energy certification; Cooling demand; Heating demand; Energy performance of buildings; Decarbonisation of building blocks